Voice compression using discrete cosine transform and wavelet transform (2019)
Compressing information, such as voice, allows freeing up memory space, better utilizing bandwidth, in other words taking advantage of resources more efficiently in a time where technologies such as Voice over Internet Protocol are booming and the demand for information it requires higher speeds and quality. Therefore, this paper presents the acquisition and digital processing of voice signals, as well as the application of the discrete cosine transform and the wavelet transform using Matlab software version 2017b, licensed by the Technological University of Bolivar. Likewise, a criterion is established in order to eliminate little relevant information without affecting the quality of the output signal for which indicators such as the signal to noise ratio and the mean square error are calculated. © Published under licence by IOP Publishing Ltd.